Exploring porphyrins induced carbon nanocone TM-PICNC (TM = Sc2+, Ti2+, V2+, Cr2+, Fe2+, Co2+, Ni2+, Cu2+, and Zn2+) as a highly sensitive sensor for CO2 gas detection in presence O2 and H2O molecules: a computational study - Wu, Guizhou; Arshadi, Sattar; Pouralimardan, Omid; Abbasi, Vahideh; Vessally, Esmail (Frontiers in Chemistry, 2023)
This study investigated the adsorption of CO2 molecules on transition metal ions (TM) porphyrins induced carbon nanocone (TM-PICNC) (TM = Sc2+, Ti2+, V2+, Cr2+, Fe2+, Co2+, Ni2+, Cu2+, and Zn2+) using density functional theory (DFT) to determine the stabilities, energetic, structural, and electronic properties. The results showed that the CO2 molecule is adsorbed on TM-PICNC with adsorption energies ranging from 0.03 to −12.12 kcal/mol. The weak interactions of CO2 gas with Cr, Ni, Cu, and Zn-PICNC were observed, while strong adsorption was found on Sc, Ti, and V-PICNC. The Ti, V, and Cr-PCNC structures were shown to have a suitable energy gap (Eg) for sensing ability because of the effective and physical interaction between these structures and CO2 gas, leading to a short recovery time. DFT calculations also revealed that V-PCNC had a high %ΔEg (about %56.79) and hence high sensitivity to CO2 gas, making it a promising candidate for having good sensing ability to CO2 gas in presence of O2 and H2O gas.